Implementation of a Mini Bank Laboratory as a Banking Simulation Tool at Wearnes Education Center - Ladystya Dwi Leonita Amalia Putri (IJBAMS: International Journal of Business Accounting Management Social Science, 2026)
This study aims to analyze the implementation of a mini bank laboratory as a banking simulation tool at Wearnes Education Center, identify the challenges encountered during its implementation, and examine its contribution to the development of students’ banking competencies in supporting industry readiness. This study employed a qualitative descriptive approach involving 15 informants consisting of 10 students, 3 lecturers, and 2 mini bank laboratory administrators selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the mini bank laboratory effectively supports practice-based learning by providing students with direct experience in banking operational activities such as account opening, transaction recording, customer service, and financial administration. These simulation activities contribute to the improvement of both technical competencies and soft skills required in the modern banking industry, including communication skills, teamwork, service orientation, and self-confidence. The study also highlights the role of mini bank laboratories in bridging the gap between theoretical learning and the competency demands of the banking sector, particularly in the context of increasing digital banking transformation. However, several challenges were identified, including limited facilities, insufficient integration with digital banking systems, and limited competencies of laboratory administrators in operating technology-based banking simulations. The novelty of this study lies in its focus on the implementation process and competency development within a vocational banking education context linked to industry needs. The practical implication of this study emphasizes the importance of strengthening digital infrastructure, enhancing human resource competencies, and integrating industry-oriented banking technology into vocational learning systems to improve graduates’ work readiness.